Kalamay sang kabuhi the historical development of the muscovado sugar industry in Laua-an, Antique (1930-2000). - Nietes, Jayson A (2004.)
The Historical Development of Muscovado Sugar Industry in Laua-an, Antique, examines the early beginnings, the growth and the present state of muscovado sugar industry of the town. The focus of the study will be on the factors that led to the existence of the small sugar mills in the town, the problems that threatened the industry, and the adaptive measures and changers it had undertaken, which were necessary for its survival., Due to the scarcity of available written matrials about the topic, the researchers relied mostly on the interviews as the primary source of valuable information. Majority of the respondents were sugar mill owners, sugarcane planters, or both. A small number from various government agencies were also considered, Problem on the exact period of origin of the industry was inevitable due to the absence of written sources and reliance mostly on interviews on selected respondents. Though, the generally accepted fact is that the industry was already present in Laua-an even before the arrival of those efficient iron machineries such as the iron rollers and the crude-driven engines, probably during the early decades of the 19th century. The reasons why muscovado industry still thrives in Laua-an are the following: 1) the topographical characteristics of the town wherein a considerably large area of land is suitable for sugarcane cultivation, 2) the enduring industry of muscovado by products such as "bandi" amking and other local candy industry in the town and lastly, 3) the deeply rooted values on inherited family business. The common problems of Muscovado Industry in Laua-an are almost the same as the problems confronted by the muscovado sugar producers in other places which are: 1)the absence of capital, 2)the declining quality of sugarcane , 3)lack of government support and lastly, marketing which they consider to be their most serious problem. Presently, with the implementation of the upgrading program by the local government and various concerned government agencies, the muscovado producers in Laua-an are hoping that most of these problems will be addressed, particularly in the aspect of marketing.
Research Project (Undergraduate, Bachelor of Arts in History-Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo.
Keywords: Muscovado Sugar Industry -- Laua-an, Antique